KONFLIK DAN KINERJA KARYAWAN - Sari, Santi Retno (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this paper is to examine the relationships to which leadership style (task and relations oriented leadership) moderate the impact of conflict on employee performance. Data were collected from 92 employees in different job levels. Partial least squares variance-based structural equation modeling (PLS-SEM) was used to test the relationship in the models. The results showed that task and relation conflict was associated with employee performance. The research findings also showed that leadership styles moderated the relationship between conflict and employee performance. This study offers implications for managerial practices. Practical implications and suggestions described in the paper Keywords: leadership style, conflict, performance.